The Effect of Electroplated Ni Nanocoating on Fatigue Life of 1020 AISI Low Carbon Steel - Israa Akram Hantoosh; Aliaksandr Skaskevich (Journal of Techniques)
Low carbon steel 1020 AISI has been selected in this study to show the influence of Ni Nano coating on fatigue life of this metal under fatigue loading at room temperature with a stress ratio R= -1. The prepared specimens are exposed to electroplated process using Nano nickel with 40 nm at diverse situations to improve the fatigue limit of metal. (SCHENCK PUNN) rotating bending fatigue test, hardness, tensile strength, microstructure, surface roughness and SEM, XRD diffraction tests have been completed for base metal and electroplating treated metal. The experimental results indicate that Ni nano coating by electroplating improve the fatigue life at due to steel substrates are typically polished mechanically and chemically before deposition to enhance the fatigue properties and nano nickel have fair distribution on steel surface.